2020
DOI: 10.1177/1461444820910418
|View full text |Cite
|
Sign up to set email alerts
|

Gaming alone: Videogaming and sociopolitical attitudes

Abstract: What sustains prosocial attitudes and political engagement in the era of online connectivity? Scholars disagree on whether frequent consumers of virtual entertainment disconnect from sociopolitical life. Using the Swedish Political Socialization Panel dataset and partial-pool time series methodology, I investigate the relationship between playing videogames and adolescents’ political and social attitudes over time. I find that those gamers who spend more time engaging in their favorite pastime become less inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 86 publications
0
3
1
Order By: Relevance
“…While the size of the relationships are small, it is important to note that there were no negative relationships between being a video gamer and likelihood of engagement in collective climate change action. This runs counter to studies that suggest playing video games might have a negative relationship with engagement in prosocial behavior (e.g., Bacovsky, 2021b), and provides evidence in support of studies that found positive relationships with other prosocial behaviors such as political engagement and activism (Bacovsky, 2021a; Jung, 2020). However, Study 1 does not explore the types of video gamers who might be more likely to engage in these behaviors, or why.…”
Section: Discussioncontrasting
confidence: 73%
See 2 more Smart Citations
“…While the size of the relationships are small, it is important to note that there were no negative relationships between being a video gamer and likelihood of engagement in collective climate change action. This runs counter to studies that suggest playing video games might have a negative relationship with engagement in prosocial behavior (e.g., Bacovsky, 2021b), and provides evidence in support of studies that found positive relationships with other prosocial behaviors such as political engagement and activism (Bacovsky, 2021a; Jung, 2020). However, Study 1 does not explore the types of video gamers who might be more likely to engage in these behaviors, or why.…”
Section: Discussioncontrasting
confidence: 73%
“…Additionally, Bacovsky (2021a) found that adolescent video gamers in Sweden tend to be politically engaged and discuss political issues with other video gamers, but their engagement is more likely to be in support of political groups associated with privacy and technology issues (i.e., the Swedish Pirate party) rather than social or environmental issues (i.e., the Green party). By contrast, in a separate study, Bacovsky (2021b) found that adolescents who played online games more often were less likely to be interested in political and social issues overall.…”
Section: Video Gamers As An Audience For Climate Change Communicationmentioning
confidence: 72%
See 1 more Smart Citation
“…The two had opposite effects, though; those with more positive attitudes toward gaming displayed less willingness to help -even though they were more likely to have tried out the game -while interest in the game itself correlated positively with this same variable. Considering the complexity of these relationships and (again) the small effect sizes noted, it is not prudent to connect the negative relationship to a broader pattern of socio-political disengagement among frequent gamers (Bacovsky, 2021), but this finding does highlight that persuasive games' target audiences and actual player bases still tend to exist in the overlap between those who might be interested in the game itself or the topic, and those who are interested in the medium of gaming regardless of what messages they might hold.…”
Section: Discussion Of Resultsmentioning
confidence: 99%
“…Whereas political communication textbooks through the mid-1990s typically limited the concept of political communication to news, political advertising, and political debates, contemporary scholars explore the content, psychology, and effects of any mediated form of information that might have political implications. Recent work points to the relationship between videogame play and less support for democratic and prosocial values (Bacovsky, 2021), increased postfeminist attitudes among viewers of YouTube makeup tutorials (Chae, 2019), the civic role of online meme culture (Penney, 2019), and the playful exploration of contentious issues related to gender and power on the social media platform, TikTok (Vijay & Gekker, 2021). Social scientists have also begun to explore complex phenomena such as "Black Twitter" as a place where People of Color construct (Harlow & Benbrook, 2019) and perform (Florini, 2014) racial identity and advance counternarratives (Graham & Smith, 2016).…”
Section: The "Who"mentioning
confidence: 99%